Sigilo profissional e Serviço Social: fundamentos políticos e regulamentação ética - Sousa, Charles Toniolo de (2020)
This work presents the debate on professional secrecy in Social Work from the ethical regulation process of the profession in Brazil. The objective was to identify the historical determinants that unleashed the debates that Brazilian social workers held on the topic of professional secrecy. Extensive documentary and bibliographic research was carried out on the production of Social Work about the subject from Brazil, France and the United States of America, in the period that comprises the emergence of the profession until 1965. After that period, interviews were conducted with social workers who are protagonists of national Social Work organizations in order to learn how the professional secrecy institute was discussed in the regulatory instruments of the profession in Brazil. To that end, professional secrecy was discussed in Brazilian legislation, and from then on the content started to be addressed. The regulation of professional secrecy in Social Work is related to the regulation of professions in general, a process that took place in Brazil based on the State policies for regulating work. Historical moment in which the Social Service emerges, its process of legitimation and expansion culminates in its regulation in 1957, and the approval of a Code of Professional Ethics by the Federal Council of Social Workers in 1965. During this period, the Brazilian Social Service appropriated itself of discussions on the theme that were built in the French and American Social Service, with strong neo-Tomist characteristics, and, transversally, functionalists. These theoretical conceptions produce a certain meaning to the words "secret", "secrecy" and "confidentiality" that tend to be treated as synonyms. Thus, it was necessary to seek the historical and political foundations of the emergence of professional secrecy and its heritage from Antiquity, the Middle Ages, the Absolutist period until it arrived in capitalist society. In it, social relations and the concrete conditions of the professions change with the widespread use of salaried work, and this directly impacts what is meant by secrecy, secret and confidentiality, even though there are still theoretical-philosophical confusions about these categories